Assessment of the vegetation in the squares of the city of Patos, State of Paraíba, Brazil - Delfino, Rita de Cassia Henriques; Souto, Patricia Carneiro; Henrique, Gilvanete da Silva; da Luz, Mellina Nicácio [UNESP]; da Costa, Leonardo José Silva [UNESP]; da Silva, Geovanio Alves (Universidade Federal de Santa Maria, 2025)
Green areas are elements of the urban environment that provide environmental improvements, preserve values, and benefit society. This study aimed to diagnose the vegetation present in the squares of the city of Patos, State of Paraíba, Brazil, and verify whether their vegetation cover is sufficient and in satisfactory condition. For this, the floristic survey and the measurement of individuals and the area of the squares were conducted. The individuals were classified according to botanical family, genus, species, common name, and origin. The green area index, the vegetation cover index, and the percentage of vegetation cover were calculated for the squares. A total of 817 individuals belonging to 67 species, distributed in 28 botanical families and 58 genera, were recorded in the 37 inventoried squares. As for the origin of individuals found in the urban forestry in the squares of Patos, 68.71% are exotic and 31.28% are native to Brazil. The calculated percentage of vegetation cover of the squares was considered satisfactory, but the green area index per inhabitant (0.58 m2 inhabitant−1) is below what the Brazilian Society of Urban Forestry recommends. In this context, the tree and shrub individuals present in the squares of the city of Patos, in general, are in good condition, Fabaceae is the predominant botanical family, and Azadirachta indica A. Juss is the dominant species. The native species Tabebuia aurea, Sarcomphalus joazeiro, Cenostigma pluviosum, Peltophorum dubium, and Handroanthus impetiginosus can be used in the urban forestry of squares.
Avaliação da vegetação das praças da cidade de Patos, Paraíba, Brasil
Keywords: Green area; Urban forestry; Urban tree planting